Learning safe practice by improving care: student-led intervention on oxygen prescribing in a respiratory ward. Issue 4 (November 2013) - Dolan, R; Linden, D; Johnston, T; Paterson, G; Rossi, J; Lynch, N; Arbuckle, S; MacLean, A; Davey, P
Background and objective: The primary aim of this intervention was to improve oxygen prescribing in accordance with the 2008 British Thoracic Society guidelines for the prescription of emergency oxygen in adults. Methods: Eight final year medical students reviewed the drug charts of all patients admitted to the respiratory ward on a daily basis in order to collect data on five audit questions: (1) Has oxygen (O2 ) been prescribed? (2) Has an O2 target saturation level been indicated? (3) Has O2 been prescribed as an 'as required' (PRN) or 'continuous therapy'? (4) Has the prescription been signed? (5) Has O2 been signed for in every drug round since the original prescription? Following an initial audit cycle an educational poster was distributed to all clinical staff via email and hard copies of the poster were placed strategically throughout the ward before its effectiveness was measured. Results: During the pre-intervention phase, compliance with all five measures varied from 0 to 25%. There was an increase in the variation in compliance after the poster intervention to 14–44%; however, this masked better overall compliance with all five investigative questions with figures of 44%, 39% and 42% being recorded in three of the four post-intervention days. Overall there was increased compliance with four of the five audit questions. Indeed compliance with question 3 rose from 14% to 83%. Conclusions: The poster intervention was marginally effective while also showing that students can improve prescribing in a clinical setting.